Upaya Debitur Dalam Mengatasi Kredit Macet Pada PT. Bank Danamon Simpan Pinjam Unit Pasar Pedan - Dominique Ellen; Siti Nurbaiti (Fakultas Hukum Universitas Tarumanagara, 2020)
Bank is one of the well-known financial institutions in Indonesia.. To provide legal certainty related to bank as financial institution, Law Number 10 of 1988 concerning Banking is regulated. Bank have various businesses and purposes, one of them is the effort to provide credit.. In order to provide credit, bank have a big risk, one of them is about bad credit, as experienced by Inna Ria Nuraini. How the debtor efforts in dealing with bad credit at PT. Bank Danamon Simpan Pinjam Unit Pasar Pedan is a researched problem. The research method used is descriptive normative legal research method, using secondary data and primary data as supporting data analysed qualitatively. The results of research illustrate that there are some several attempts which can be done by the debtor for dealing with their bad credit, that is by submitting restructurisation, rescheduling, or reconditioning. However, those attempts not implemented by the debtor because she prefer to bring a lawsuit to court.